Is the firearm epidemic in the US getting worse?. (30th September 2020) - Tedesco, D; Adja, K Y C; Rallo, F; Reno, C; Fantini, M P; Hernandez-Boussard, T
Abstract: Background: The US is the least regulated firearm market in the Western world and firearm violence is a major public health issue. Firearms account for 40, 000 deaths in the US annually, which is higher than other high-income countries. Although most of the gun-related deaths in the US are the result of suicide attempts and self-inflicted injuries, nearly 40% of them come from accidents, assaults, or police intervention. Methods: We measured the number of non-self-inflicted firearm-related ED visits, by including patients discharged with diagnostic ICD-9-CM (ICD-10 for 2016) codes of accidents, assaults or legal intervention resulting in firearm injuries between 2006-2016. We used data from the Healthcare Cost and Utilization Project (HCUPnet). From the CDC Wide-ranging Online Data for Epidemiologic Research we obtained data on non-suicidal firearm-related deaths over the period 2006-2017. To identify the cause of death we used the ICD-10 codes. Temporal changes of rates of ED visits and deaths were evaluated using Joinpoint Software. Results: In 2006 there were a total of 79, 998 ED visits with a diagnostic code of firearm-related injury, and this number showed a non-significant 2.7% annual decline between 2006-2013 (p = 0.06) followed by a significant 19.4% annual increase between 2013-2016 (p < 0.05), resulting in 111.305 visits in 2016. The number of non-suicidal firearm-related deaths showed a significant 2.2% annual decline between 2006-2014 (p < 0.05), followed by a significant 10.3% APC (p < 0.05) between 2014-2017. Conclusions: Data showed steady rates until 2013 and a striking increasing trend starting from 2013. Firearm-related deaths followed the same trends. Our data show that in the last four detectable years there has been a new concerning wave of gun violence and consequently a higher number of fatalities. Analysis limitations: we used national-level aggregate data and coding accuracy may be not consistent nationwide. Key messages: In the last four detectable years there has been a new concerning wave of gun violence and consequently a higher number of fatalities nationwide. The US firearm related deaths epidemic urges for new policies and preventive measures, such as stricter background checks and restrictions on guns ownership.